Sponge-like loose and porous SnO2 microspheres with rich oxygen vacancies and their enhanced room-temperature gas-sensing performance. Issue 12 (10th March 2022) - Pi, Wenbo; Chen, Xi; Humayun, Muhammad; Yuan, Yang; Lei, Yifan; Li, Xinyue; Tang, Zaiqi; Zhang, Xiaowei; Huang, Dayong; Lu, Zixiao; Li, Honglang; Zheng, Zhiping; et al.
Abstract : Sponge-like loose and porous SnO2 microspheres with rich oxygen vacancies were successfully fabricated for use in a gas sensor, which possessed extremely high response and high selectivity towards H2 S gas. Abstract : Structure and surface modification of semiconductor materials are of great importance in gas sensors. In this study, a facile citric acid-assisted solvothermal method via a precise calcination process was leveraged to synthesize sponge-like loose and porous SnO2 microspheres with rich oxygen vacancies (denoted as LP-SnO2 -Ov ). When this material was used in a gas sensor, it exhibited an extremely high response to 10 ppm hydrogen sulfide gas at room temperature ( R a / R g = 9688), which was 54 times higher than that of commercial SnO2 . Furthermore, the response time of LP-SnO2 -Ov was 5 s, while the recovery time was 177 s. Moreover, it displayed such high selectivity and stability for hydrogen sulfide gas that its properties remained almost unchanged after 1 month. This method paves a new way to fabricate materials possessing a sponge-like loose and porous structure with oxygen vacancies, which is promising for many other scientific fields such as lithium-ion batteries and photocatalysis.